2007
DOI: 10.2501/s0021849907070493
|View full text |Cite
|
Sign up to set email alerts
|

Bloggers' Motivations and Behaviors: A Model

Abstract: During the past few years, there has been an exponential growth of biogs, and behind these blogs are numerous bioggers who create and manage them, it is wideiy expected that bioggers armed with their own biogs wiii make a tremendous impact on both mass communication media and marketers who reiy on such media. However, given the widespread use of biogs, there has been iittle systematic anaiysis of the factors behind biogging activities. To serve as a stepping-stone, this articie presents a modei that addresses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 25 publications
4
95
0
5
Order By: Relevance
“…Existing research on blogs as object of study, the second category identified above, has paid attention to motivations for blogging (e.g., Huang et al, 2007), blog categories (e.g., Dearstyne, 2005), interactions between bloggers and readers (e.g., Huang et al, 2008) and the influence of employee bloggers (e.g., Aggarwal et al, 2011). Madsen (2009) …”
Section: Csr Communications and Bloggingmentioning
confidence: 99%
“…Existing research on blogs as object of study, the second category identified above, has paid attention to motivations for blogging (e.g., Huang et al, 2007), blog categories (e.g., Dearstyne, 2005), interactions between bloggers and readers (e.g., Huang et al, 2008) and the influence of employee bloggers (e.g., Aggarwal et al, 2011). Madsen (2009) …”
Section: Csr Communications and Bloggingmentioning
confidence: 99%
“…A blog is a website presenting dated entries, or posts, containing either text, images, or audio/video and typically listed in reverse-chronological order (Huang, Shen, Lin, & Chang, 2007;Miller & Pole, 2010;Nardi, Schiano, Gumbrecht, & Swartz, 2004b;Schiano, Nardi, Gumbrecht, & Swartz, 2004), most taking the form of an online diary (Nardi, Schiano, & Gumbrecht, 2004a) with fairly brief posts (Schiano et al, 2004). Initially, keeping a blog required knowledge of programming, but with introduction of user-friendly free services such as Blogger and WordPress, anyone with internet access can start and maintain a blog (Huang et al, 2007;Miller & Pole, 2010).…”
Section: What Are Family Building Blogs?mentioning
confidence: 99%
“…3 People are motivated to keep personal blogs to document their lives, express thoughts and opinions, for catharsis, and community. 1,7 Regardless of their reasons for posting, bloggers may share their personal opinions and feelings on the Internet to online audiences, who may read and comment on their blogs. That is, bloggers may selfdisclose and communicate with unknown audiences, based on trust, 15 anonymity, 16 or both.…”
Section: Self-disclosure In Real Life and In Cyberspacementioning
confidence: 99%